ANALISIS PENDAYAGUNAAN GENERATIVE ARTIFICIAL INTELEGENCE (GAI) OLEH GURU SD KOTA DENPASAR: PERSPEKTIF ETIKA, EFISIENSI, & EFEKTIVITAS - Dewa Made Dwicky Putra Nugraha; Priantini, Dewa Ayu Made Manu Okta; Juniayanti, Dewi; Satria, Agus; Andriani, Ni Gusti Ayu (UHN IGB Sugriwa Denpasar, 2025)
The utilization of artificial intelligence (AI) in primary education is a transformative global phenomenon, yet it highlights the urgency of integrating this technology responsibly and effectively. Previous research indicates gaps in the ethical analysis, teacher time efficiency, and empirical impact on student learning outcomes. Therefore, this study aims to comprehensively assess the use of generative AI by elementary school teachers in Denpasar City from ethical, efficiency, and effectiveness perspectives concerning students. This study applying a quantitative descriptive approach with a cross-sectional survey design, data were collected from 142 elementary school teachers in Denpasar City via an online questionnaire using a Likert scale (1-5). The questionnaire comprised 12 ethics items, 8 efficiency items, and 9 effectiveness items. Descriptive analysis and Pearson correlation were performed. Results indicate that elementary school teachers in Denpasar selectively utilize generative AI (e.g., ChatGPT, Canva AI, Quizziz AI) according to specific pedagogical needs. Teachers' perceptions of the ethics (mean = 3.58), efficiency (mean = 3.70), and effectiveness (mean = 3.63) of AI use were categorized as